CASH FLOWS FROM OPERATING ACTIVITIES AND EFFECTIVENESS OF DAIRY CATTLE FARMS IN BULGARIA - Tsvetana HARIZANOVA-METODIEVA; Tatiana IVANOVA; Verginia GAIDARSKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the research was to estimate cash flows from operating activities of dairy cattle farms in Bulgaria and to compare their effectiveness. In order to achieve the aim, in 2016, information was collected by questionnaires from 2 dairy farms located in Northern Bulgaria. The first farm had 16 cows in the main herd, and the second farm had 120 cows respectively. A number of indicators had been studied: farm size (number of animals, arable land and pasture in decares), animal feed, milk production, number of calves born and fattened, cleaning technologies used in the farms, animal health, cash flows by categories. An estimate of the cash flows from operating activities of the dairy cattle farms had been developed. The estimate was based on the collected information and on the basis of own calculations. The farm with 120 cows in the main herd achieved higher effectiveness than the farm with the smaller herd, although the farm with 16 cows managed 50 decares more arable land, achieved higher average milk yield (7,000 l vs. 6,000 l) and received subsidies. Workforce involved with cattle operations in the first farm was used less effectively compared with that in the second farm: a cattleman tended for an average of 8 cows in the main herd in the first farm and for 30 cows in the second farm.